(3ebGdI aj HjGf GdNWC GdYGQV aj eYfi ePchQ aj GdebGdI GdKGdKI ef cJGH GdSeGA hGdYGdes - (3CHh GdaJhM fLe GdOjf CMeO Hf eMeO Hf GdSQj GdHZOGOj, GHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3bGd bO cfJ deG GfJgi di GdfXQ Edi CKfGA GdebGdI GdKGdKI ef cJGH CQSWh WGdjS ai GdSeGA hGdYGde ai GdehVY GdPi jQO ajg Ydi GdPjf jTcdhf GdGSWbSGJ s
(3BNQgG (B:s
(3aEPkG djS hGMO ef GdCTcGd GdNeSI JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs